Effect of Salinity Stress on Concentrations of Nutrition Elements in Almond (Prunus Dulcis) 'Shokofeh', 'Sahand' Cultivars and '13-40' Genotype Budded on GF677 Rootstock - A. Momenpour (Majallah-i ̒Ulum-i Bāghbānī, 2016)
Introduction: Almond (Prunus amygdalus B.) is one of the most important crops consumed as a dry fruit and it is mainly adaptable to arid and semi-arid regions mostly suffering from salinity stress (8). Soils with dry humidity regime are dominant in Iran and in the world at large and mostly include regions with more evaporation than precipitation. This in turn leads to increased salinity of the soil (9 and 10). Based on available reports, roughly 12.5% of land areas in Iran are saline, which overwhelmingly contain sodium, while more than 800 million hectares of land area on the earth (6% of overall global land area) are affected by salinity (9 and 10). Therefore, compound of rootstock and scion may be used as one of the influence factors in sensitivity or tolerance to salinity of planted fruit trees including almonds (8 and 11). In recent years, for various reasons including the uniformity of trees, instead of sexual rootstock, vegetative rootstock is used. Rootstock GF677 an inter-specific hybrid (Almond Peach) is propagated asexually as clone (8). It has been reported that rootstock GF677 is tolerant to salinity while rootstock nemagard (P. persica X P. davidiana) is sensitive to salinity (16). It has been reported that rootstock GF677 tolerated salinity (5.5 ds/m), (19) or 5.2 ds/m (17 and 14).However, as plant species and different cultivars within the same plant species vary considerably in their tolerance to salinity (10), properly selecting plants and/or cultivars that can be grown well under adverse conditions, created in the root zone by salinization, is the most efficient and environmentally friendly agricultural practice for a more permanent solution of the problem of salinity (10). Despite the presence of information on the effect of salinity on concentration of nutrition elements of almond cultivars leaves and roots, tolerantscion/rootstock combinationshave not been introduced for this plant. Therefore, the aim of the present study is to evaluate the effects of salt stress on concentration of nutritional elements of selected almond genotypes leaves and roots, grafted on GF677 rootstock and introducing most tolerant genotypes to it. Materials and Methods: In this research, the effects of salinity stress were investigated on nutrient of almond leaves and roots by a completely randomized design (CRD), with two factors, genotype (in the four levels) and irrigation water salinity (in the five levels) with tree replications in the research greenhouse of Seed and Plant Institute in the year 2013. Studied Genotypes included ‘Shokofeh’, ‘Sahand’ and ‘13-40’ budded on GF677 and ‘GF677’ (none budded as control) and irrigation water salinity included 0, 1.2, 2.4, 3.6 and 4.8 g/l of natural salt (whose electrical conductivity are equal to 0.5, 2.5, 4.9, 7.3 and 9.8 ds/m, respectively).Nutrition elements such as K+, Ca++, Mg++, P, Na+, Cl-, Zn++, Cu++, Fe++, Na+to K+ ratio, Na+ to Ca++ ratio, Na+ to Mg++ ratio, Na+ to P ratio, were investigated in selected almond genotypes leaves and roots. Then salinity stress was applied. Results and Discussion:The results showed that type of scion and level of salinity had affected nutrient concentration of leaves and roots. Evaluation of nutrition elements concentration in leaves and roots showed that in the total studied genotypes, the highest percentage of Na+, Cl-, Na+to K+ ratio, Na+ to Ca++ ratio, Na+ to Mg++ ratio, Na+ to P ratio and the lowest percentage of Ca++, Mg++, P and concentration of Cu++ in leaves and roots and the lowest concentration of Zn++ in leaves were observed in treatment 9.8 ds/m. The result showed that the type of scion was effective in obstruction of Na+absorptionby therootsand their transportationtoleaves.Percentageof Na+, Cl-, Na+ to K+ ratio and Na+ to P ratio in levels of salinity 3.6 and 4.8 g/l and Na+ to Ca++ ratio, Na+ to Mg++ ratio in level of salinity 4.8 g/l in ‘Shokofeh’ cultivar were significantly lessthan other genotypes. Also, this cultivar could compare with control plants at levels of salinity 3.6 and 4.8 g/l by increasing the percentage of K+and concentration of Fe++ ,and it could tolerate the harmful effects of Na+ more than other genotypes. Conclusion: Overall, the results showed that both rootstock and type of scion were effective in tolerance to salinity. GF677 rootstocks (non-budded) tolerated salinity of 2.4 g/l (4.9 ds/m), but withincreasingsalt concentration, plants were severely damaged. The results showed that the type of scion affected tolerance to salinity. In this research,at base concentration of nutritional elements,‘Shokofeh’ cultivar was the most tolerant cultivar against salinity stress. This cultivar could well tolerate salinity of 3.6 g/l (7.3 ds/m) and partly salinity 4.8 g/l (9.8 ds/m). In contrast, Sahand cultivar was the most sensitive cultivar to salinity stress. These cultivar as GF677 rootstocks (non-budded as control) only could tolerate salinity of 2.4 g/l.